INFLUENCE OF THE DRYING ON THE SCOPOLETIN INDUCTION OF CASSAVA CHIPS PRODUCED IN BENIN. - GBAGUIDI, A. (My University, 2016)
The production of cassava chips in Benin is a very common traditional activity. Previous studies on the conservation of these chips have shown the presence of scopoletin in the fresh roots and a significant increase of this substance after six days of sun drying. The objective of the present investigation was to determine the effect of drying on the induction of scopoletin of cassava chips. Four cassava varieties were dried using five different methods. Water content of chips obtained showed that sun drying on grid method at room temperature removed the maximum amount of water. The determination of scopoletin content by HPLC revealed the mean values ranging from 5.87 to 12.89 mg / kg for the fresh roots. After six days of drying, these contents increased significantly regardless of the drying method used. The study showed that the drying is a major factor promoting the accumulation of scopoletin. The method of sun drying on grid at room temperature indicates the highest scopoletin content and the lowest moisture content regardless of the cassava root variety studied